2014
DOI: 10.3389/fpsyg.2014.00925
|View full text |Cite
|
Sign up to set email alerts
|

Mood, food, and obesity

Abstract: Food is a potent natural reward and food intake is a complex process. Reward and gratification associated with food consumption leads to dopamine (DA) production, which in turn activates reward and pleasure centers in the brain. An individual will repeatedly eat a particular food to experience this positive feeling of gratification. This type of repetitive behavior of food intake leads to the activation of brain reward pathways that eventually overrides other signals of satiety and hunger. Thus, a gratificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
217
1
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(247 citation statements)
references
References 383 publications
(560 reference statements)
10
217
1
19
Order By: Relevance
“…Negative emotional states trigger the consumption of palatable foods with high hedonic value, providing positive gratification and comfort (Singh, 2014). However, repeated consumption of these palatable energy-dense foods, usually high in carbohydrates, sugar, and fat, increases the likelihood of obesity, and substantiates the need to clarify how affective state can impact our health.…”
Section: Introductionmentioning
confidence: 97%
“…Negative emotional states trigger the consumption of palatable foods with high hedonic value, providing positive gratification and comfort (Singh, 2014). However, repeated consumption of these palatable energy-dense foods, usually high in carbohydrates, sugar, and fat, increases the likelihood of obesity, and substantiates the need to clarify how affective state can impact our health.…”
Section: Introductionmentioning
confidence: 97%
“…Reward and gratification associated with palatable food consumption are partially mediated by abrupt dopamine (DA) increases in the nucleus accumbens and the ventral tegmental area (Singh, 2014). Moreover, the amount of DA released after consuming a preferred meal eventually correlates with the degree of experienced pleasure (Small, Jones‐Gotman, & Dagher, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that people who are depressed tend to eat comfort food to elevate their mood, thereby leading to obesity [181]. Depression can occur in adults, children and adolescents.…”
Section: G Psychological Factorsmentioning
confidence: 99%